2003
DOI: 10.1046/j.1464-410x.2003.04208.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and medical management of stone disease

Abstract: SUMMARYRecurrent stone formation in the urinary tract is a common and important problem that must be considered in daily urological practice. With a prevalence of> 10% and an expected recurrence rate of ≈ 50%, stone disease has an important effect on the healthcare system. It is generally agreed that patients with uric acid/urate, cystine or infection stones always should be treated pharmacologically. For calcium stone formers the treatment should be chosen according to the severity of the disease. Recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(141 citation statements)
references
References 66 publications
1
129
0
11
Order By: Relevance
“…Recurrent stone formation in the urinary tract is a common and important finding that should be considered in clinical nephrology practice (1). Recent international literature data suggest rising incidence and prevalence rates of renal lithiasis, reaching values from 10 to 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent stone formation in the urinary tract is a common and important finding that should be considered in clinical nephrology practice (1). Recent international literature data suggest rising incidence and prevalence rates of renal lithiasis, reaching values from 10 to 15%.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier the recurrence rate of kidney stones is approximately 15% in the first year and as high as 50% within five years of the initial stone. 65 Effective kidney stone prevention is dependent on the stone type and the identification of risk factors for stone formation. An individualized treatment plan incorporating dietary changes, supplements, and medications can be developed to help prevent the formation of new stones.…”
Section: Preventionmentioning
confidence: 99%
“…67 Stone formers should not be advised to restrict calcium unless it has been shown that they have an excessive intake of calcium. 65 A reduced intake of calcium leads to an increased intestinal absorption of oxalate, which itself may account for an increased risk of stone formation. Vitamin C has been implicated in stone formation because of in vivo conversion of ascorbic acid to oxalate.…”
Section: Preventionmentioning
confidence: 99%
“…Urolithiasis is a worldwide health problem (1, 2) which typically affects the social life of the patients during their most active and productive age between 20 and 50 years (3,4). In addition to the distressing pain, obstruction and recurrent infections, decreased productivity, loss of work time are the adverse outcomes of stone disease (5,6).…”
Section: Introductionmentioning
confidence: 99%